Quae natura caduca est: Cicero and Lucretius on Ecological Change - Matlock, Andres (Ciceroniana On Line, 2023)
Although starting from a common metaphor of vegetal descent (caducus), Lucretius and Cicero offer distinct perspectives on ecological change – that is, how species, particularly plants and humans, develop and relate to each other over time. Especially in the final two books of De rerum natura, Lucretius sketches a narrative of dwindling terrestrial fertility that closes off future reproduction via intraspecies lineages. By contrast, Cicero’s eco-writing in De senectute as well as the last book of De finibus, leaves open the possibility of interspecies fertility – what I call “feralization” – that can overcome the shared fallenness of plants and humans. To draw a conclusion out of this divergence, I propose an analogy between these ancient perspectives on the future and the horizons of the texts themselves by considering their reception history from our own crisis of eco-fertility.